Seasonal Variations and Characterization of Solid Aerosols Related to Faisalabad (Pakistan) Environment - Muhammad Attique Khan Shahid; Khadim Hussain; Mariam Saeed Awan (Journal of Basic & Applied Sciences, 2012)
Black solid aerosols were monitored continuously at Faisalabad using Gaussian dispersion model and nucleation model. Data for one year 2006 was analyzed here keeping in view the meteorological and climatological conditions of Faisalabad co-relating them with concentration gradient. Winter has minimum concentration, i.e. equivalent to background level followed by summer (598.80 μmg/m3), Moon Soon (2762.00 μmg/m3) and finally Post Moon Soon (8863.00 mg/m3). Temperature and pressure gradients both were negative co-relationed with black solid aerosols. These results were not in accordance with other studies, the reason may be the complexity of the Faisalabad environment on account of its geographical, geological and industrial setup confirmed by longitudinal, latitudinal effects and mix plume behavior. A positive co-relationship between biomass burning and seasonal variation i.e. low concentration of particulate matter i.e., 637.30 μg/m3 in summer and high in winter such as 3954 μg/m3.